Pengaruh Desain Kantin terhadap Fleksibilitas Kegiatan Mahasiswa Universitas Matana - Calvin Rinaldi Ocktavius; Louis Alexandra (Prodi Arsitektur Universitas Matana, 2019)
Canteen is one place to meet food needs in the campus environment, besides the price is affordable by students, the place is also affordable, which is located within the campus environment. Even though the price is cheap and affordable, the hygiene of food sanitation must be kept in mind. The purpose of this study was to identify the sanitation hygiene conditions of food handlers in the canteen of the matana university campus, Tangerang based on the Regulation of the Minister of Health of the Republic of Indonesia Number 1096 / MENKES / PER / VI / 2011 concerning Jasaboga Sanitary Hygiene. In addition, the canteen is expected to be a place to accommodate other students' activities, this place can be flexible to all activities carried out by students in it.